2007
DOI: 10.1186/1471-2288-7-42
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting and retaining GPs and patients in intervention studies: the DEPS-GP project as a case study

Abstract: Background: Recruiting and retaining GPs for research can prove difficult, and may result in sub-optimal patient participation where GPs are required to recruit patients. Low participation rates may affect the validity of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 11 publications
(24 reference statements)
7
87
0
3
Order By: Relevance
“…Our results are also in line with previous surveys that reported relatively low prevalence of major depression in older age (Trollor et al, 2007), although subsyndromal depression may be more common and perhaps as disabling (Snowdon, 2001), suggesting that future studies might need to take such a factor into account. Finally, our data were derived from a trial of education of general practitioners (GPs) about depression and self-harm behavior (Williamson et al, 2007). Data from the trial showed that the intervention was not associated with a decline in the prevalence of depression, although it did reduce suicide ideation (Almeida et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are also in line with previous surveys that reported relatively low prevalence of major depression in older age (Trollor et al, 2007), although subsyndromal depression may be more common and perhaps as disabling (Snowdon, 2001), suggesting that future studies might need to take such a factor into account. Finally, our data were derived from a trial of education of general practitioners (GPs) about depression and self-harm behavior (Williamson et al, 2007). Data from the trial showed that the intervention was not associated with a decline in the prevalence of depression, although it did reduce suicide ideation (Almeida et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding the recruitment have been reported elsewhere (Williamson et al, 2007;Almeida et al, 2011). Between May and December 2005, each patient aged 60 years or over of participating primary care practices was sent a questionnaire.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Details regarding the recruitment of general practitioners and their patients have been reported elsewhere (Williamson et al, 2007). Between May and December 2005 each patient on the practice list was sent a self-completion questionnaire, a personalized cover letter from their general practitioner, project information, a consent form and a reply-paid envelope addressed to the project office.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The qualitative interviews in practices comprised a low proportion of GPs and a higher proportion of reception staff. This could reflect the reported difficulties in getting GPs to engage with the initiative, or a more general reluctance of GPs to take part in research, which is well documented (Borgiel et al, 1989;Silagy and Carson, 1989;Bell-Syer and Moffett, 2000;Askew et al, 2002;Williamson et al, 2007). It could, alternatively, be seen as being appropriate to the way the initiative was implemented, as receptionist triage was consistently adopted within the practices, while changes involving GPs were rather less prominent.…”
Section: Methodological Limitationsmentioning
confidence: 99%